보조항암화학치료 후 발생한 항이뇨호르몬분비이상증후군 - 조재화; Jae Hwa Cho; 윤용한; Young Han Yoon; 곽승민; Seung Min Kwak; 이홍렬; Hong Lyeol Lee; 김광호; Kwang Ho Kim; 백용수; Yong Soo Baek; et al. (Tuberculosis and respiratory diseases, 2006)
항이뇨호르몬분비이상증후군(이하 SIADH)은 암환자의 항암화학치료 시 드물게 관찰된다. 저자 등은 선암으로 진단받고, 좌폐하엽 절제술 시행 후 보조항암화학치료 중인 51세 여자 환자에서 발작을 동반한 SIADH 1예를 문헌고찰과 함께 보고하는 바이다. We report a case of pulmonary adenocarcinoma complicated by the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) following adjuvant chemotherapy. A 51-year-old woman with stage ⅢA adenocarcinoma received left lower lobe lobectomy in July, 2006. And then combination chemotherapy with paclitaxel and cisplatin was given to the patient. In five days after completion of second cycle of the chemotherapy, she visited emergency room because of general weakness and seizure. Her brain MRI was shown to be no evidence of brain metastasis. Serum sodium, urine and plasma osmolarities were 117mEq/L, 589 and 244mOsm/kg, respectively. She was improved with fluid restriction. Although occurrence of SIADH following chemotherapy is rare, physician should give an attention the potential for development of SIADH in the course of chemotherapyin non-small cell lung cancer patient. (Tuberc Respir Dis 2006; 61: 591-594)